MODULATION OF PARASITEMIA AND ANTIBODY-RESPONSE TO TRYPANOSOMA-CRUZI BY CYCLOPHOSPHAMIDE IN CALOMYS-CALLOSUS (RODENTIA, CRICETIDAE) - Borges, M. M.; Curi, P. R.; Kloetzel, J. K. (Inst Medicina Tropical, 1992)
Calomys callosus a wild rodent, previously described as harboring Trypanosoma cruzi, has a low susceptibility to infection by this protozoan.Experiments were designed to evaluate the contribution of the immune response to the resistance to T. cruzi infection exhibited by C. callosus. Animals were submitted to injections of high (200 mg/kg body weight) and low (20 mg/kg body weight) doses of cyclophosphamide on days -1 or -1 and +5, and inoculated with 4 x 10(3) T. cruzi on day O. Parasitemia, mortality and antibody response as measured by direct agglutination of trypomastigotes were observed. Two hundred mg doses of cyclophosphamide resulted in higher parasitemia and mortality as well as in suppression of the antibody response. A single dose of 20 mg enhanced antibody levels on the 20th day after infection, while an additional dose did not further increase antibody production. Parasitemia levels were not depressed, but rather increased in both these groups as compared to untreated controls. Passive transfer of hyperimmune C. callosus anti-T. cruzi serum to cyclophosphamide immunosuppressed animals resulted in lower parasitemia and mortality rates. These results indicate that the immune response plays an important role in the resistance of C. callosus to T. cruzi.
Keywords: CALOMYS-CALLOSUS; CYCLOPHOSPHAMIDE; TRYPANOSOMA-CRUZI; PARASITEMIA; MORTALITY; ANTIBODY RESPONSE